Predicting morphological and functional variations of benign adrenal incidentalomas in relation to initial characteristics - Parazzoli, Chiara; Favero, Vittoria; Aresta, Carmen; Morelli, Valentina (Frontiers in Endocrinology, 2023)
The follow-up strategy for unresected non-functional adrenal tumors (NFAT) is a major controversial issue in endocrinological clinical practice, as the natural history of adrenal incidentalomas (AI) is partially unknown and a consensus on their adequate management is lacking. In a recent longitudinal study by Ceccato et al., a large cohort of patients with conservatively treated AI were evaluated for possible radiological variations over time and their relationship with autonomous cortisol secretion (ACS). Starting from this paper, we performed a literature review of available longitudinal studies focus on the same issue. Notwithstanding the high variability in the duration of follow-up and in the criteria used to define ACS in the included studies, our findings support the idea that there is a not negligible risk of morphological and functional changes, which may have metabolic implications, especially after 5-10 years of follow-up. Unfortunately, these variations seem to be scarcely predictable. Therefore, it may be risky to interrupt the follow-up in patients with NFAT, in particular in the presence of larger diameter of the adenoma and higher cortisol levels at diagnosis. These results should be considered in defining the optimal management of these patients.